Digital Innovation, Indigenous Knowledge, and Sustainable Cultural Policy - Nazaruddin, M. Arief; Handaru, Wuri Cahya (Indonesian Scientific Publication, 2024)
This study explores sustainability in arts management and cultural policy through a comprehensive narrative review of interdisciplinary literature. The objective was to examine how sustainability is conceptualized and operationalized across global contexts, with particular attention to governance structures, institutional practices, digital innovation, and indigenous knowledge. Methodologically, the review employed targeted searches in Scopus, Web of Science, and Google Scholar, using key terms such as “cultural policy,” “arts management,” “sustainability,” and “cultural governance.” Inclusion criteria prioritized peer-reviewed studies published between 2000 and 2025 that engaged directly with sustainability in cultural sectors. Selected works were analyzed through narrative synthesis to identify recurring themes and divergent findings. The results reveal four key dimensions of sustainability in cultural policy. First, global trends show that sustainability principles are increasingly embedded in cultural strategies, though implementation varies between developed and developing countries. Second, institutional practices highlight the importance of autonomy, adaptability, and innovative funding models such as crowdfunding. Third, digital transformation emerges as a powerful tool for enhancing access, participation, and heritage preservation. Fourth, indigenous and local knowledge provide culturally grounded frameworks that enrich policy inclusivity and effectiveness. These findings indicate that sustainable cultural governance requires balancing economic viability with cultural authenticity and social justice. The implications emphasize the need for adaptive policies, interdisciplinary approaches, and expanded geographical research. Strengthening political commitment, fostering multi-stakeholder collaboration, and recognizing cultural diversity are essential strategies to overcome systemic barriers. This review contributes to advancing the global dialogue on sustainable cultural governance and highlights pathways for research and practice to ensure the resilience of arts and cultural sectors.